PERAN TUAN GURU DALAM PENYADARAN HUKUM PEMBAYARAN NAFKAH ‘IDDAH PERCERAIAN DI LUAR PENGADILAN - Qamar, Abdul Hafiz; Nasir, Moh. Abdun; Supriadi, L. (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
This research is motivated by the writer’s anxiety about phenomena which occurs in society related to the fulfillment of nafkah 'iddah obligations after divorce carried out outside the Religious Court, especially through the Tuan Guru's decision in Labuapi District. The objectives of this research were 1) to analyze the distribution of nafkah 'iddah in the divorce outside the court in Labuapi District, 2) to analyze the factors which influenced the law awareness level in providing nafkah 'iddah to the community, 3) to analyze the form and role of Tuan Guru in socializing the fulfillment of nafkah 'iddah obligations to the community. This research was field research, the research method used was qualitative research. Data collection techniques were carried out with observation, interviews and documentation. The results of this research showed that the distribution of nafkah 'iddah in Labuapi District was not carried out properly, it was based on the lack of society’s knowledge, traditions were applied in society, and because of conflicts between husband and wife which caused the divorce. In addition, in this research the writer found 2 active roles of Tuan Guru in the community, namely, 1) as a Ulama' (Islamic religious leader) who provides understanding to the community, 2) as a mediator and consultant for Family Law.